Rating species sensitivity throughout gradient systems – a consistent approach for the Baltic Sea. (February 2016) - Schiele, Kerstin S.; Darr, Alexander; Zettler, Michael L.; Berg, Torsten; Blomqvist, Mats; Daunys, Darius; Jermakovs, Vadims; Korpinen, Samuli; Kotta, Jonne; Nygård, Henrik; von Weber, Mario; Voss, Joachim; et al.
Highlights: Species sensitivity values are calculated for 329 macrozoobenthic species in the Baltic Sea. 19 subsets consider environmental gradients and sampling effects for sensitivity values. Sensitivity values are publicly available to improve transparency of environmental assessments. Abstract: Evaluating the state of benthic communities has played an important role in water quality assessments. Indices incorporating species sensitivities, richness and densities are commonly applied. In Europe, the importance of benthic indices has increased in the last years with the implementation of the European Marine Strategy Framework Directive (MSFD) which at the same time demands the applicability of an index across regional scales. To date, environmental variability is rarely considered in benthic indices and most sensitivity rankings have the disadvantages of static values (i.e. the same value in all areas), expert judgement and a limited geographical range. This study presents species sensitivity values calculated along environmental gradients for the Baltic Sea. Sensitivities were calculated according to the procedure of the Benthic Quality Index (BQI). We created a matrix of subregions, classes of salinity, depth and gear to identify comparable subsets for data analysis. Altogether, 19 subsets were defined within the Baltic Sea basins. Sensitivity values were calculated for 329 species out of a total of 678 species that were recorded in this study. Sensitivity values of taxa vary between subsets as it was expected for different environmental conditions. Most sensitivity values can be assigned to species occurring in euhaline and polyhaline waters. Distribution of species with high and low sensitivity values differed along the salinity gradient. In euhaline waters more species with high sensitivity values occurred than species with low sensitivity values, while in mesohaline waters the ratio of high and low sensitivity values among species was almost equal. In oligohaline waters more species with lower sensitivity values were present. For the first time, sensitivity values were calculated for a large number of species using the same method for the entire Baltic Sea. This results in a Baltic-wide comprehensive set of sensitivity values based on a dataset across subregional borders, and divided along environmental gradients and gear type. The same principles can be applied to transient waters from rivers to coastal lagoons as well as to other environments with gradients of, e.g. hydrodynamic characteristics. Publicly available sensitivity values will increase transparency and support the improvement of state assessments under the MSFD.